A culture-based public relations perspective on the traditional performing art of “Caci” - Manafe, Yermia Djefri; Andung, Petrus Ana; Ali, Mohd Nor Shahizan (PRofesi Humas, 2025)
Background: Caci performance art is a vital cultural asset of the Manggarai community in East Nusa Tenggara Province. However, the rapid advancement of internet-based technologies poses a significant threat to the survival of traditional forms of folk media, including Caci as a traditional game. As such, an effective communication strategy is essential to preserving the noble cultural values embedded in Caci and promoting its significance to a broader audience. Purpose: This study explored the forms of culture-based public relations activities associated with Caci and analyzed the communicative functions of art within this context. Methods: The study used an ethnographic approach. The informant’s involvement in this research includes serving as a primary source during interviews, guiding participant observations, and consulting on research findings to ensure the accuracy of the data. Results: The findings indicated several culture-based public relations activities linked to Caci, including community relationship-building, bentang cama as a forum for planning, Caci as a vehicle to reinforce the masculinity of Manggarai men, post-performance evaluation, and public communication regarding the cultural significance of Caci. Conclusion: Caci performance art encapsulates key components of public relations, encompassing the stages of fact-finding, planning, communication, and evaluation. These stages reinforce the role of Caci as a tool for executing culture-based public relations strategies. Furthermore, the Caci ritual, as a traditional performance serves as social, magical-religious, and entertainment functions. Implications: Public relations research can be expanded through a cultural perspective aligned with local community values. Additionally, traditional performing arts like Caci can be effective tools in PR strategies, fostering innovative, culturally grounded approaches. The study also emphasizes the need to preserve and promote traditional arts as essential to cultural identity in the face of advancing internet technology.